2009
DOI: 10.1038/ijir.2009.55
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of testosterone gel in the treatment of erectile dysfunction in hypogonadal hemodialysis patients: a pilot study

Abstract: End-stage renal disease (ESRD) affects sexual function. The etiology of sexual dysfunction in ESRD is multifactorial and hypogonadism is not uncommon. In a cohort of 96 men with ESRD, scores on International Index of Erectile Function (IIEF) correlated with bioavailable testosterone (T; Po0.01). We further evaluated the effects of administration of T on ED in hypogonadal men on hemodialysis. Nine men with ED and hypogonadism (baseline bioavailable T o3.82 nmol l À1 ), received 5 g T-gel (1% (10 mg g À1 ) per d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 32 publications
2
14
1
Order By: Relevance
“…However, in these studies, many of the patients who received testosterone were not frankly hypogonadal. In agreement with this, a recent noncontrolled study in 9 HD male patients with hypogonadism showed that therapy with transdermal testosterone gel effectively restored testosterone levels to the normal range, and significantly improved erectile function, sexual desire, orgasmic function and overall sexual satisfaction (134). Although nowadays androgen supplementation is seldom used for the treatment of anemia in ESRD, some studies have shown that the combination of intramuscular androgens and rhEPO increased hemoglobin levels beyond the effect of either alone (77,(135)(136)(137).…”
Section: Dopaminergic Agonistsmentioning
confidence: 64%
“…However, in these studies, many of the patients who received testosterone were not frankly hypogonadal. In agreement with this, a recent noncontrolled study in 9 HD male patients with hypogonadism showed that therapy with transdermal testosterone gel effectively restored testosterone levels to the normal range, and significantly improved erectile function, sexual desire, orgasmic function and overall sexual satisfaction (134). Although nowadays androgen supplementation is seldom used for the treatment of anemia in ESRD, some studies have shown that the combination of intramuscular androgens and rhEPO increased hemoglobin levels beyond the effect of either alone (77,(135)(136)(137).…”
Section: Dopaminergic Agonistsmentioning
confidence: 64%
“…Cabergoline and bromocryptine reduce serum prolactin levels and either can be used in selected patients (Biller et al 1996). Testosterone gel has been successfully used in the treatment of erectile dysfunction in hypogo‐nadal haemodialysis patients (Cangüven et al 2010). Alternative options in the management of the erectile dysfunction are vacuum tumescence device and administration of zinc (Lessan‐Pezeshki & Ghazizadeh 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Contra-indications include the presence of prostate cancer or palpable prostatic nodules, PSA above 4 ng/ml, untreated severe obstructive sleep apnea, and prostatic hypertrophy causing severe lower urinary tract symptoms. Benefits of correcting hypogonadism might include improvements in ED, as evidenced by two small uncontrolled case series (105, 106), although a third study found little gain from treatment (107). …”
Section: Management Of Sexual Dysfunction In Ckdmentioning
confidence: 99%